Optimizing Quality of Life with Cognitive Impairment: A Study of End-of-Life Care in Assisted Living - Arneson, Laura (J Am Med Dir Assoc, 2019)
OBJECTIVES: Assisted living (AL) is an expanding site of end-of-life (EOL) care in the US. Understanding determinants of quality of life (QoL) for AL residents near EOL is vital to optimize care for this growing population, most of whom have some degree of cognitive impairment (CI). This analysis aimed to identify factors associated with QoL in a diverse sample of AL residents with CI approaching EOL. DESIGN: Observational cross-section design. SETTING AND PARTICIPANTS: Data are from a 5-year study funded by the National Institute on Aging examining EOL care of residents in 7 diverse AL communities in metropolitan Atlanta (n=67). METHODS: CI was assessed with the Montreal Cognitive Assessment (MoCA) (scores ≤ 26) and QoL was determined with the self-reported QoL in Alzheimer’s disease (QoL-AD) survey adapted for use in AL. Psychological distress was assessed using the PHQ-4 and fatigue was assessed using the 13-item FACIT-Fatigue scale questionnaire. Initial descriptive analyses were followed by backward stepwise regression analyses to select a best-fitting model of QoL. RESULTS: The final model predicted 27% of the variance in QoL. CI was not significantly correlated with QoL and was not retained in the final model. Pain and functional limitation also did not meet inclusion criteria (p ≤ 0.10) and were sequentially removed, producing a final model of QoL in terms of psychological distress (β=−.28, p=.032), fatigue (β=−.26, p=.048), and race (β=.21, p=.063). CONCLUSIONS AND IMPLICATIONS: The lack of a significant correlation between degree of CI and self-reported QoL suggests that AL residents have the potential to experience high QoL, despite CI. Interventions to reduce psychological distress and manage fatigue could be implemented during EOL care to attempt to improve QoL for AL residents with CI. The correlation between race and QoL warrants investigation into possible racial disparities in AL and EOL care.